Edukasi Serta Pendampingan Budidaya Cacing ANC Dan Produksi Pelet Industri Rumahan Di Desa Wonosari Kabupaten Deli Serdang - Ilham Mubaraq Ritonga; Azwansyah Habibie; Dody Hidayat (LPPM STIKOM Tunas Bangsa, 2022)
This Educational and Assistance activity for ANC Worm Cultivation and Home Industry Pellet Production is a Community Partnership Program activity involving partners, namely the Deli Serdang Worm Farmers Association (ATC Deli Serdang) located in Wonosari Village, Tanjung Morawa District, Deli Serdang Regency. Priority issues related to production processes, financial management, not yet producing downstream products that are attractive to the market, and marketing processes. The learning and mentoring method provide solutions: (1) Increasing the production of ANC Worms in new ways and using technology with the